Method for preparing fluorescent material based on waste NCM ternary lithium battery and application of fluorescent material
By preparing manganese-doped perovskite fluorescent materials, the problem of expensive and complex operation of chloride ion detection equipment in wastewater is solved, and the resource recycling and on-site detection of waste NCM ternary lithium batteries is realized, providing a low-cost and efficient chloride ion detection method.
Patent Information
- Application Number
- CN202510432317.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-07-04
AI Technical Summary
The existing chloride ion detection methods and equipment in wastewater are expensive, cumbersome, time-consuming and cannot be tested on-site, and the waste NCM ternary lithium battery resources have not been effectively recycled.
By disassembling the waste NCM ternary lithium battery, extracting nickel-cobalt-manganese lithium waste into powder, and after acid solution and precipitant treatment, lithium, nickel and cobalt ions are removed to obtain manganese-containing powder, mixed with the first perovskite fluorescent raw material, ligand and solvent for heating and stirring, adding the second perovskite fluorescent raw material solution to react, and preparing manganese-doped perovskite fluorescent material for preparation of chloride ion detection test paper.
It realizes efficient recycling and utilization of waste NCM ternary lithium batteries, reduces the cost of fluorescent materials preparation, and provides a simple and low-cost on-site chloride ion detection method, with high detection accuracy and high sensitivity, and can quickly judge the chloride ion concentration.
Smart Images

Figure CN120248865A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a fluorescent material from waste NCM ternary lithium batteries and an application of the fluorescent material, belonging to the technical field of chloride ion detection. Background Art
[0002] Chlorine element widely exists in nature and can be classified into natural sources and anthropogenic sources according to its origin. In natural sources, chlorine element exists in underground rock formations and the ocean, and is released through crustal movement, water flow and evaporation. In anthropogenic sources, petrochemical, papermaking and spinning, thermal power generation and leather products enterprises are prone to generate chlorine-containing wastewater. The total amount and concentration of chlorine-containing wastewater discharged by these enterprises are ecological problems that cannot be ignored. In addition, a large amount of chlorine-containing wastewater is generated in fields such as machinery manufacturing, metallurgy and mining.
[0003] Chloride ions present in wastewater can cause serious harm to enterprise production. For example, enterprise equipment or pipelines are often made of stainless steel to prevent corrosion. However, if the chloride ions in the water used in production exceed the standard, it will cause serious corrosion to the equipment and pipelines, endanger the service life of the equipment and increase the safety risk. When the removal of chloride ions in industrial wastewater does not meet the standard, the chloride ions entering the water body will endanger the water quality. Chlorides formed by the combination of calcium, aluminum and other ions with chloride ions are extremely harmful to algae and fish in the water. After the wastewater infiltrates into the soil, it will also harm the crops on the soil. Trace amounts of chloride ions can promote the growth of crops, increase the absorption of trace elements such as silicon, calcium, nitrogen and potassium, and improve the quality and yield of crops. However, when the chloride ion content in the soil exceeds the standard, it will affect the absorption of nutrients and water by crops, thereby causing a decrease in crop yield. If the chloride ion content in the human body is too high, it will cause osteoporosis due to calcium metabolism.
[0004] Currently, the concentration of chloride ions in wastewater is mainly detected by methods such as chemical titration, electrochemistry, spectroscopy, chromatography, etc. The detection equipment used in these methods is expensive, the detection operation is cumbersome, the time is long, the requirements for detection personnel are high, and on-site detection cannot be carried out. Therefore, there is an urgent need to develop a new material with simple operation, low cost and capable of on-site detection. Summary of the Invention
[0005] The object of the present invention is to provide a method for preparing a fluorescent material based on waste NCM ternary lithium batteries and the application of the fluorescent material, aiming to solve the problems existing in the existing methods for detecting chloride ions in wastewater, such as expensive equipment, cumbersome operation, long time consumption, high requirements for testers and inability to perform on-site detection. At the same time, it realizes the efficient recycling of waste NCM ternary lithium batteries, reduces the preparation cost of the fluorescent material, improves the resource recycling rate, reduces environmental pollution, and provides a new fluorescent material with simple operation, low cost and capable of being used for on-site detection and its application.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a fluorescent material based on waste NCM ternary lithium batteries, comprising the following steps:
[0008] S1. Disassemble the waste NCM ternary lithium battery, obtain the lithium nickel cobalt manganese oxide waste and make it into powder;
[0009] S2. Dissolve the lithium nickel cobalt manganese oxide waste powder in an acid solution, then add a precipitant and stir. After solid-liquid separation, an leaching solution is obtained;
[0010] S3. After removing nickel, cobalt and lithium ions in the leaching solution, evaporate the liquid phase, and crush the obtained precipitate to obtain a manganese-containing powder;
[0011] S4. Mix the manganese-containing powder, the first perovskite fluorescent raw material, the ligand, the protective material and the solvent, heat and stir under vacuum conditions, then heat up in a nitrogen atmosphere and add the second perovskite fluorescent raw material solution to the system for reaction. After cooling, a manganese-doped perovskite fluorescent material is obtained.
[0012] Preferably, the acid solution is one or more of hydrochloric acid, hydrobromic acid, hydroiodic acid, sulfuric acid, nitric acid, phosphoric acid, hydrofluoric acid, acetic acid, oxalic acid and lactic acid;
[0013] The solid-liquid ratio of the lithium nickel cobalt manganese oxide waste powder and the acid solution is 50 - 300 g / L.
[0014] Preferably, the precipitant is hydrogen peroxide, peracetic acid or a solution containing one or more of potassium permanganate, potassium dichromate, sodium peroxide and potassium peroxide;
[0015] And the concentrations of potassium permanganate, potassium dichromate, sodium peroxide and potassium peroxide in the solution are 0.01 - 0.7 g / ml respectively;
[0016] The dosage of the precipitant is 0.5 - 1.5 times the volume of the acid solution.
[0017] Preferably, the lithium ions in the leaching solution are removed by precipitation with choline stearate;
[0018] Nickel ions are adsorbed and removed using ion exchange resin;
[0019] Cobalt ions are extracted and removed using an extractant.
[0020] Preferably, the addition ratios of the manganese-containing powder, the first perovskite fluorescent raw material, the ligand, the protective material, the solvent, and the second perovskite fluorescent raw material solution are:
[0021] (0.001 - 0.02) g : (0.1 - 1.5) mmol : (0.5 - 5) ml : (0.05 - 0.5) ml : (8 - 20) ml : (0.05 - 0.5) ml;
[0022] And the concentration of the second perovskite fluorescent raw material in the second perovskite fluorescent raw material solution is 0.1 - 0.8 mmol / ml;
[0023] In step S4, the conditions for heating and stirring are: 100 - 150 °C, 800 - 1200 rpm, 20 - 50 min;
[0024] The target temperature for heating up is: 160 - 200 °C, and the heating rate is 1 - 5 °C / min.
[0025] Preferably, the first perovskite fluorescent raw material is at least one of lead bromide, lead chloride, lead iodide, lead carbonate, lead nitrate, and ammonium chloride, ammonium bromide, ammonium iodide;
[0026] The second perovskite fluorescent raw material solution is a solution containing at least one of cesium bromide, cesium chloride, cesium iodide, cesium carbonate, cesium nitrate;
[0027] And the first perovskite fluorescent raw material and the second perovskite fluorescent raw material solution contain lead ions, cesium ions, and at least one halogen ion.
[0028] Preferably, the ligand is one or more of oleic acid, oleylamine, stearic acid, octadecylamine, polyacrylic acid, polystyrenic acid, polyethylene glycol, polyethylene diamine, didodecyldimethylammonium bromide, amino acid, 4-(aminomethyl)pyridine, and sodium dodecylbenzenesulfonate.
[0029] Preferably, the protective material is one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrapropyl titanate, and tetrabutyl titanate.
[0030] Preferably, the solvent is one or more of 1-octadecene, dimethyl sulfoxide, dimethylformamide, acetonitrile, toluene, acetone, n-hexane, cyclohexane, octane, methyl acetate, and ethyl acetate.
[0031] Application of the fluorescent material prepared by any of the above methods in chloride ion detection.
[0032] The beneficial effects of the present invention are as follows:
[0033] 1. The recycling technology of waste NCM ternary lithium batteries has a certain compatibility with the preparation technology of manganese-doped perovskite fluorescent materials, which plays a role in cost saving and performance enhancement during the preparation of perovskite fluorescent materials.
[0034] 2. For the discarded NCM ternary lithium batteries, after the positive electrode materials inside the batteries are recycled through effective means and used to prepare manganese-doped perovskite fluorescent materials, the recycling rate of resources is improved, and environmental pollution is reduced to a certain extent. At the same time, the recycling of manganese in the positive electrode materials can effectively reduce the preparation cost of manganese-doped perovskite fluorescent materials, which is of great significance for the preparation and popularization of the application of new optoelectronic devices.
[0035] 3. The manganese ion-doped perovskite fluorescent material prepared by this method has high fluorescence efficiency, and its stability meets the requirements of chloride ion detection test strips.
[0036] 4. When testing the chloride ion concentration with the chloride ion test strip, the operation is convenient, the detection time is short, the cost is low, the test strip is sensitive to the added chloride ions, the fluorescence color change is obvious, and the position change of the main fluorescence peak is obvious.
[0037] 5. The chloride ion detection test strip can detect the chlorine-containing wastewater with a concentration range of 0 - 10000 mg / L, and can quickly determine the chloride ion concentration range in the wastewater by the naked eye, with an accuracy of more than 93%. By measuring the chloride ion concentration through the position of the fluorescence peak, the accuracy is more than 98%. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Optical photographs of the solution containing the fluorescent material prepared in Example 1 under (a) natural light and (b) ultraviolet light, and (c) fluorescence spectrum;
[0039] Figure 2 TEM photograph of the fluorescent material prepared in the example;
[0040] Figure 3 Optical photographs of the chloride ion detection test strip prepared in Example 1 under (a) natural light and (b) ultraviolet light excitation;
[0041] Figure 4 Standard curve of chloride ion concentration and fluorescence peak position, with the formula y = -0.0045x + 489.38, R 2 = 0.998. Wherein, y represents the wavelength of the main fluorescence peak, and x represents the chloride ion concentration;
[0042] Figure 5Optical photographs of the solution containing the fluorescent material prepared in Comparative Example 1 (a) under natural light and (b) under ultraviolet light, and (c) fluorescence spectrum;
[0043] Figure 6 Optical photographs of the chloride ion test strips prepared in Comparative Example 1 (a) under natural light and (b) under ultraviolet light excitation, and (c) optical photograph of the test strip after adding a chloride ion solution under ultraviolet light;
[0044] Figure 7 Fluorescence colorimetric card for chloride ion test strips;
[0045] Figure 8 Optical photographs of the aged chloride ion test strips prepared in Comparative Example 2 (a) with 3-aminopropyltriethoxysilane added and (b) without 3-aminopropyltriethoxysilane added after reacting with a chloride ion solution under ultraviolet light excitation;
[0046] Figure 9 Optical photographs of the reaction between the chloride ion solution and the test strip in Comparative Application Example 2 (a) under ultraviolet light excitation and (b) fluorescence spectrum. Detailed implementation mode
[0047] Example 1
[0048] Disassemble the waste NCM ternary lithium battery to obtain lithium nickel cobalt manganese oxide waste powder. Weigh 2 g of lithium nickel cobalt manganese oxide waste powder and dissolve it in 10 ml of hydrobromic acid (47 wt%). Then add 5 ml of hydrogen peroxide (hydrogen peroxide), let it stand for 2 h, and then separate the solid and liquid. Add 0.5 g of choline stearate to the collected supernatant and stir. After standing, separate the solid and liquid to remove lithium ions. The obtained supernatant is adsorbed by 0.1 g of polyamine-type chelating resin to remove nickel ions, and then 0.1 g of Cyanex 272 is added to extract and remove cobalt ions. Subsequently, centrifuge at 10000 rpm for 10 minutes to obtain a manganese bromide solution. After heating and evaporating the solvent of the manganese bromide solution at 80 °C, manganese bromide powder is obtained.
[0049] Weigh 0.4 mmol of lead bromide, 0.0020 g of the manganese bromide powder prepared above, 10 ml of 1-octadecene, 1.0 ml of oleic acid, 1.0 ml of oleylamine, and 0.1 ml of 3-aminopropyltriethoxysilane, and place them in a three-necked flask. Under vacuum conditions at 120 °C, stir at a speed of 10000 rpm for 30 minutes, then introduce nitrogen and heat up to 180 °C at a heating rate of 3 °C / min. Immediately inject 0.2 ml of a cesium oleate solution with a concentration of 0.5 mmol / ml into the three-necked flask and react for 5 seconds. Take it out and cool it in an ice-water bath. Add 12 ml of methyl acetate to the solution, stir, centrifuge at 10000 rpm for 10 minutes in a centrifuge and collect the precipitate. Add 10 ml of toluene to the precipitate, stir, centrifuge at 10000 rpm in a centrifuge for 10 minutes and collect the supernatant containing the fluorescent material (the optical photos of which under natural light and ultraviolet light excitation are shown in regions a and b of Figure 1 respectively, and show green color and green fluorescence. Its fluorescence spectrum is shown in region c of Figure 1 . The peak located at 497 nm belongs to the fluorescence peak of the perovskite matrix, and the peak located at 601 nm belongs to the fluorescence peak of manganese. The transmission electron microscope photo of the prepared fluorescent material is shown in Figure 2 . The rod-shaped crystals therein are the morphology of manganese-doped perovskite).
[0050] Immerse the absorbent pad in the above-mentioned supernatant containing the fluorescent material, take it out, dry it, and cut it into a chloride ion detection test paper of 6*2 cm (the optical photos of the chloride ion detection test paper under natural light and ultraviolet light are shown in regions a and b of Figure 3 respectively, and show yellow color and green fluorescence).
[0051] Using deionized water as the solvent and sodium chloride as the chlorine source, prepare chloride ion solutions with concentrations of 0, 2000, 4000, 6000, 8000, and 10000 mg / L. Respectively take 0.1 ml of the above-mentioned chlorine-containing solutions and drop them on the chloride ion detection test paper to react for 30 seconds. After the reaction is completed, take a photo of the fluorescence color of the test paper under an ultraviolet lamp and make a standard fluorescence colorimetric card. Use an instrument to detect the fluorescence spectrum of the test paper. Draw a standard curve based on the main fluorescence peak position and chloride ion concentration. The formula is y = -0.0045x + 489.38, R 2 = 0.998. Where y = the main fluorescence peak position, in nm, x = the chloride ion concentration, in mg / L (the standard curve is shown in Figure 4 . The abscissa is the chloride ion concentration, and the ordinate is the fluorescence peak wavelength).
[0052] Comparative Example 1
[0053] The difference from Example 1 is that when preparing the chloride ion detection test paper, the manganese bromide powder prepared by recycling NCM ternary lithium batteries was not added.
[0054] The prepared supernatant containing the fluorescent material is green under natural light and shows green fluorescence under ultraviolet light excitation. The fluorescence peak is located at 520 nm (optical photos of the perovskite fluorescent material under natural light and ultraviolet light excitation are shown in regions a and b of Figure 5 , showing green color and green fluorescence respectively. Region c in the figure is the fluorescence spectrum diagram, and the peak located at 520 nm is the fluorescence peak of the perovskite).
[0055] Optical photos of the chloride ion detection test paper prepared with the perovskite fluorescent material without manganese under natural light and ultraviolet light excitation are shown in regions a and b of Figure 6 , where region a shows yellow color and region b shows green fluorescence.
[0056] After the chloride ion detection test paper prepared without manganese bromide reacts with different chloride ion solutions, the fluorescence color can only show a change from green to blue, and there are only 2 types of color changes, namely green and blue, as shown in Figure 6 . Region c is the optical photo of the test paper under ultraviolet light excitation after testing for chloride ions. After the chloride ions react with the fluorescent material on the test paper, the fluorescence changes from green to blue.
[0057] However, for the perovskite fluorescent material prepared by adding manganese bromide powder, there are fluorescence peaks of the matrix and manganese ions in the fluorescence spectrum. After the chloride ions at different concentrations react with the detection test paper, the test paper shows a mixture of the fluorescence of the doped perovskite matrix and the fluorescence color of manganese ions, and there will be up to 6 types of fluorescence color changes. This enables an intuitive judgment of the concentration range of chloride ions in the chlorine-containing wastewater by comparing the fluorescence color changes with the standard fluorescence color comparison card (as shown in Figure 7 , where the 6 color blocks from top to bottom are the fluorescence colors of the chloride ion detection test paper prepared with manganese-doped perovskite after reacting with chloride ion solutions of 0, 2000, 4000, 6000, 8000, and 10000 mg / L respectively. The formula at the bottom is the relationship curve between the chloride ion concentration and the fluorescence peak position, R 2 = 0.998).
[0058] Comparative Example 2
[0059] The difference from Example 1 is that 3-aminopropyltriethoxysilane was not added during the preparation of the manganese-doped perovskite fluorescent material.
[0060] The chloride ion detection test strips prepared in Example 1 and Comparative Example 2 were placed in an aging oven and kept at a temperature of 80 °C for 30 days. The purpose was to compare whether the test strips could show fluorescence changes when used after long-term storage. After testing, the chloride ion detection test strip added with 3-aminopropyltriethoxysilane still showed a change in fluorescence color after dropping the chloride ion solution, while the chloride ion detection test strip without 3-aminopropyltriethoxysilane no longer showed fluorescence after dropping the chloride ion solution. The reason for this phenomenon is that 3-aminopropyltriethoxysilane forms a silica protection layer during the preparation of the perovskite fluorescent material. This protection layer can protect the fluorescent material from the influence of heat on its fluorescence performance and will not affect the reaction of the chloride ion solution passing through the protection layer with the perovskite material during the subsequent reaction process. Therefore, the chloride ion detection test strip added with 3-aminopropyltriethoxysilane still has excellent chloride ion detection accuracy after long-term storage (the two reacted test strips are as Figure 8 shown. Among them, region a is the optical photograph under ultraviolet light excitation after dropping the chloride ion solution on the chloride ion detection test strip prepared with 3-aminopropyltriethoxysilane, showing blue fluorescence. Region b is the optical photograph under ultraviolet light excitation after dropping the chloride ion solution on the chloride ion detection test strip prepared without 3-aminopropyltriethoxysilane, showing no fluorescence).
[0061] Application Example 1
[0062] Take 0.1 ml of chlorine-containing wastewater (the actual chloride ion concentration detected by inductively coupled plasma emission spectrometry is 9500 mg / L) and drop it on the chloride ion detection test strip prepared in Example 1. After reacting for 30 seconds, observe the fluorescence color of the test strip under an ultraviolet lamp, which is dark blue. Subsequently, compare it with the standard fluorescence color card and read the chloride ion concentration in the simulated wastewater with an unknown concentration as 9000 mg / L, and the detection accuracy reaches 94.7%. Perform fluorescence spectroscopy detection on the test strip, and the positions of the main fluorescence peaks are 447 nm respectively. Substitute them into the above formula to calculate the chloride ion concentration as 9417 mg / L, and the detection accuracy reaches 99.12%.
[0063] Application Example 2
[0064] Take 0.1 ml of chlorine-containing wastewater (the actual chloride ion concentration detected by inductively coupled plasma emission spectroscopy is 6405 mg / L), drop it on the chloride ion test paper prepared in Example 1, after reacting for 30 seconds, observe the fluorescence color of the test paper under ultraviolet light, which is pink. After comparing with the standard fluorescence color card, the chloride ion concentration is obtained as 6000 mg / L. Use a fluorometer to detect the fluorescence spectrum of the test paper. The result shows that the wavelength of the main fluorescence peak is 461 nm. Substitute it into the formula to calculate that the chloride ion concentration is 6306 mg / L. The detection accuracy by comparing the fluorescence color of the test paper with the standard fluorescence color card is 93.67%, and the detection accuracy by formula calculation is 98.45% (the optical photo of the reacted test paper under ultraviolet light excitation is as shown in Figure 9 region a in, where the unreacted region shows green fluorescence, and the region after adding chloride ions to react shows pink fluorescence. The fluorescence spectrum diagram of the pink fluorescence region is as shown in region c, where the peak at 467 nm is the fluorescence peak of the perovskite matrix, and the peak at 602 nm is the fluorescence peak of manganese ions).
[0065] The above is only the preferred embodiment of the present invention patent. It should be pointed out that for those of ordinary skill in the art, without departing from the principle of the present invention patent, several improvements and retouches can be made, and these improvements and retouches should also be regarded as the protection scope of the present invention patent.
Claims
1. A method for preparing a fluorescent material based on waste NCM ternary lithium batteries, characterized in that, It includes the following steps: S1. Disassemble the waste NCM ternary lithium battery, obtain the lithium nickel cobalt manganese oxide waste and make it into powder; S2. Dissolve the lithium nickel cobalt manganese oxide waste powder in an acid solution, then add a precipitant and stir. After solid-liquid separation, obtain the leaching solution; S3. After removing nickel and cobalt lithium ions in the leaching solution, evaporate the liquid phase, and crush the obtained precipitate to obtain manganese-containing powder; S4. Mix the manganese-containing powder, the first perovskite fluorescent raw material, the ligand, the protective material and the solvent, heat and stir under vacuum conditions, then raise the temperature under a nitrogen atmosphere and add the second perovskite fluorescent raw material solution to the system for reaction. After completion, cool to obtain the manganese-doped perovskite fluorescent material.
2. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, wherein The acid solution is one or more of hydrochloric acid, hydrobromic acid, hydroiodic acid, sulfuric acid, nitric acid, phosphoric acid, hydrofluoric acid, acetic acid, oxalic acid and lactic acid; The solid-liquid ratio of the lithium nickel cobalt manganese oxide waste powder to the acid solution is 50 - 300 g / L.
3. The method for preparing the fluorescent material based on the waste NCM ternary lithium battery according to claim 1, wherein, The precipitant is hydrogen peroxide, peracetic acid or a solution containing one or more of potassium permanganate, potassium dichromate, sodium peroxide and potassium peroxide; And the concentrations of potassium permanganate, potassium dichromate, sodium peroxide and potassium peroxide in the solution are 0.01 - 0.7 g / ml respectively; The dosage of the precipitant is 0.5 - 1.5 times the volume of the acid solution.
4. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, wherein Lithium ions in the leaching solution are removed after precipitation with choline stearate; Nickel ions are removed by adsorption with an ion exchange resin; Cobalt ions are removed by extraction with an extractant.
5. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, wherein The addition ratio of the manganese-containing powder, the first perovskite fluorescent raw material, the ligand, the protective material, the solvent and the second perovskite fluorescent raw material solution is: (0.001 - 0.02) g : (0.1 - 1.5) mmol : (0.5 - 5) ml : (0.05 - 0.5) ml : (8 - 20) ml : (0.05 - 0.5) ml; And the concentration of the second perovskite fluorescent raw material in the second perovskite fluorescent raw material solution is 0.1 - 0.8 mmol / ml; In step S4, the conditions for heating and stirring are: 100 - 150 °C, 800 - 1200 rpm, 20 - 50 min; The target temperature for raising the temperature is: 160 - 200 °C, and the heating rate is 1 - 5 °C / min.
6. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, wherein, The first perovskite fluorescent raw material is at least one of lead bromide, lead chloride, lead iodide, lead carbonate, lead nitrate and ammonium chloride, ammonium bromide, ammonium iodide; The second perovskite fluorescent raw material solution is a solution containing at least one of cesium bromide, cesium chloride, cesium iodide, cesium carbonate, cesium nitrate; And the first perovskite fluorescent raw material and the second perovskite fluorescent raw material solution contain lead ions, cesium ions and at least one halogen ion.
7. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, wherein, The ligand is one or more of oleic acid, oleylamine, stearic acid, octadecylamine, polyacrylic acid, polystyrenic acid, polyethylene glycol, polyethylene diamine, didodecyldimethylammonium bromide, amino acid, 4-(aminomethyl)pyridine and sodium dodecylbenzenesulfonate.
8. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, wherein, The protective material is one or more of tetramethyl orthosilicate, tetraethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrapropyl titanate and tetrabutyl titanate.
9. The method for preparing a fluorescent material based on waste NCM ternary lithium batteries according to claim 1, characterized in that, The solvent is one or more of 1-octadecene, dimethyl sulfoxide, dimethylformamide, acetonitrile, toluene, acetone, n-hexane, cyclohexane, octane, methyl acetate and ethyl acetate.
10. Use of the fluorescent material prepared by the method according to any one of claims 1-9 in chloride ion detection.
Citation Information
Cited By
High-performance degradable magnesium alloy prepared from waste lithium-containing battery, preparation method of high-performance degradable magnesium alloy and application of high-performance degradable magnesium alloy in soluble bridge plug
CN121653436A
Method for preparing high-performance magnesium-lithium alloy through alloying of positive electrode material of waste lithium ion battery
CN122235472A
Method for preparing regenerated magnesium, aluminum and copper alloy through alloying of positive electrode material of waste lithium ion battery
CN122235473A